A Novel Digital Watermarking Method for New Viewpoint Video Based on Depth Map - Ning Zhu; Guiguang Ding; Jianmin Wang (2008 Eighth International Conference on Intelligent Systems Design and Applications, 2008)
With the development of the theory of new viewpoint generation, a lot of methods such as GBR(geometry-based rendering) and IBR (image-based rending) became hot subjects. However, there isn't any watermarking method for them. In this paper, we propose firstly a watermarking method for the new viewpoint video frame generated by DIBR (depth image-based rendering). For the sake of preserving the watermark info during the generation of the new viewpoint video frame, we choose the blocks in foreground object of original video frame to embed the watermark since pixels in this kind of object are more probably to be preserved in the warping, therefore the watermark could also be preserved well. The experiment results have proved that the proposed watermarking method may solve the watermarking problem of new viewpoint video frame generated by DIBR without affecting the quality of the image much.